Modeling the developmental trajectories of rational number concept(s). (June 2015) - McMullen, Jake; Laakkonen, Eero; Hannula-Sormunen, Minna; Lehtinen, Erno
Abstract: The present study focuses on the development of two sub-concepts necessary for a complete mathematical understanding of rational numbers, a) representations of the magnitudes of rational numbers and b) the density of rational numbers. While difficulties with rational number concepts have been seen in students' of all ages, including educated adults, little is known about the developmental trajectories of the separate sub-concepts. We measured 10- to 12-year-old students' conceptual knowledge of rational numbers at three time points over a one-year period and estimated models of their conceptual knowledge using latent variable mixture models. Knowledge of magnitude representations is necessary, but not sufficient, for knowledge of density concepts. A Latent Transition Analysis indicated that few students displayed sustained understanding of rational numbers, particularly concepts of density. Results confirm difficulties with rational number conceptual change and suggest that latent variable mixture models can be useful in documenting these processes. Highlights: 3rd–6th graders showed little conceptual development with rational numbers. Representational knowledge was necessary but not sufficient for density knowledge. Latent Transition Analysis was effective for modeling development over 1 year. Developmental patterns are explained with conceptual change theory.